2017
DOI: 10.1021/acs.orglett.7b01213
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylate Anions Accelerate Pyrrolidinopyridine (PPy)-Catalyzed Acylation: Catalytic Site-Selective Acylation of a Carbohydrate by in Situ Counteranion Exchange

Abstract: Acylpyridinium ions have been known as catalytically active species in acylation reactions catalyzed by 4-dimethylaminopyridine and its analogues. Acylpyridinium carboxylates were found to be 800-1300 times more reactive than the corresponding acylpyridinium chlorides. A catalytic cycle was developed, in which acylpyridinium carboxylates were generated by in situ counteranion exchange from the acylpyridinium chlorides. A catalyst loading as low as 0.01 mol % and catalyst turnover number of up to 6700 were achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…The preparation of high value‐added carbohydrates and building blocks for oligosaccharide synthesis still remains the most important scientific problem in carbohydrate chemistry . Regioselective acylation is of great importance in the synthesis of valuable oligosaccharide structural units because it facilitates the protection and deprotection of hydroxyl groups and the synthesis of target building blocks . Recently, many methods have been developed to make regioselective acylations highly efficient, green, and even controllable, and some metal catalysts and organic small molecules have been used for the regioselective acylation of carbohydrates and diols; for example, tin(IV), boron(IV), copper(II), silver(I), and iron catalysts have been recently reported , .…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of high value‐added carbohydrates and building blocks for oligosaccharide synthesis still remains the most important scientific problem in carbohydrate chemistry . Regioselective acylation is of great importance in the synthesis of valuable oligosaccharide structural units because it facilitates the protection and deprotection of hydroxyl groups and the synthesis of target building blocks . Recently, many methods have been developed to make regioselective acylations highly efficient, green, and even controllable, and some metal catalysts and organic small molecules have been used for the regioselective acylation of carbohydrates and diols; for example, tin(IV), boron(IV), copper(II), silver(I), and iron catalysts have been recently reported , .…”
Section: Introductionmentioning
confidence: 99%
“…[3] Direct, selective functionalization of minimally protected (or nonprotected) carbohydrates (1!2,Scheme 1a)provides rapid access to derivatives of these compounds,a nd thus attracts significant attention from the synthetic community. Tr emendous progress [4][5][6][7][8] has been made in this area, and some representative,e legant strategies are summarized in Scheme 1a.One general strategy involves the use of organoborinic acids 3,o rganotin reagents 4,o ro ther Lewis acidic catalysts. [5] Catalysts of this type often function by chelating with a cis-1,2-diol motif in ac arbohydrate scaffold, and selectively activate the equatorial hydroxy group toward electrophiles.Another classical strategy is based on the use of organocatalysts with ag eneral structure such as 5:T hese catalysts contain aLewis basic moiety (e.g., aNheterocycle) to activate electrophilic reagents and as ubstrate-recognition moiety to guide the reagent to the site of the reaction.…”
mentioning
confidence: 99%
“…[5] Catalysts of this type often function by chelating with a cis-1,2-diol motif in ac arbohydrate scaffold, and selectively activate the equatorial hydroxy group toward electrophiles.Another classical strategy is based on the use of organocatalysts with ag eneral structure such as 5:T hese catalysts contain aLewis basic moiety (e.g., aNheterocycle) to activate electrophilic reagents and as ubstrate-recognition moiety to guide the reagent to the site of the reaction. [6] More recently,c hiral phosphoric acids 6 were also shown to be useful for the site-selective modification of carbohydrates. [7] These strategies exhibited remarkable value in transformations such as acylation, phosphorylation, sulfonylation, sily-lation, and glycosylation reactions.S elective alkylation was also possible under slightly more forcing conditions.H owever,c ritical deficiencies in this area still exist.…”
mentioning
confidence: 99%
“…It was observed that upto 99 % yield and 98 % site selectivity can be obtained under the developed reaction conditions. The methodology was realized by using a catalyst loading of 0.01 mol % with a turnover number (TON) of 6700 (Scheme ) …”
Section: Pyridine Derivatives As Organocatalystsmentioning
confidence: 99%